Progress in the diagnostics and treatment of myomata uteri - Bulsa, Marek; Kozłowska, Urszula; Czaja-Bulsa, Grażyna (Przewodnik Lekarza/Guide for GPs, 2012)
Women suffer from myomata uteri at every stage of life. Myomata uteri (fibroid tumors) are the most frequent reason for of gynocological operations. The author presents issues related to their diagnosis prophylaxis and ways of treatment.